PEMAKNAAN KOMUNIKASI BUDAYA MASYARAKAT SUNDA: (STUDY FENOMENOLOGI PEMAKNAAN KATA SAMPURASUN PADA REMAJA) - Deri Hudaya Deri; Haryadi Mujianto; Iis Zilfah Adnan; Gantha Pagarsandya (Prodi Ilmu Komunikasi Universitas Putera Batam, 2022)
The objective of this research is analyze the motives, meanings and experiences experienced by Garut youth in the use of the sentence